Ocean acidification promotes otolith growth and calcite deposition in gilthead sea bream (Sparus aurata) larvae - Coll-Lladó, Clara; Giebichenstein, Jan; Webb, Paul B.; Bridges, Christopher R.; Garcia de la Serrana, Daniel (Scientific Reports, 2018)
This work received funding from the Marine Alliance for Science and Technology for Scotland (MASTS) Small Grant initiative (SG330 and SG407). MASTS is funded by the Scottish Funding Council (grant reference HR09011) and contributing institutions. PBW would like to thank the Royal Society for the award of an Industry Fellowship. Financial support to CRB and JG were through the BIOACID (Biological Impacts of Ocean Acidification; Phase II) research programme. The effects of ocean acidification on otolith crystallization and growth rates were investigated in gilthead sea bream (Sparus aurata) larvae. Larvae were exposed to three different pH levels: pH8.2, pH7.7 and pH7.3 for a period of 18 days post-fertilization. For the first time, we demonstrate that pH has a significant impact on the carbonate polymorph composition, showing calcite in a significant percentage of individuals at low pH. Around 21% of the larvae exposed to pH7.3 showed irregular calcitic otoliths rather than commonly found round aragonitic otoliths. Calcitic otoliths showed a moderate level of heritability suggesting an important role of genetic factors. We also observed significantly larger otoliths in larvae reared at pH7.7 and pH7.3 compared to pH8.2 in both sagittae and lapilli. Our results demonstrate that otolith growth rates in gilthead sea bream larvae increase at low pH while a significant proportion of larvae are prone to the formation of calcitic otoliths at pH7.3. Peer reviewed